2014
DOI: 10.2340/00015555-1803
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in Epithelial Differentiation and Development are Differentially Expressed in Oral and Genital Lichen Planus Epithelium Compared to Normal Epithelium

Abstract: Lichen planus (LP) is a chronic mucocutaneous disease with unknown cause. Patients with LP often have both oral and genital lesions, but these conditions are often considered as separate diseases and treated accordingly. To find out which genes are differently expressed in mucosal LP compared to normal mucosa and establish whether oral and genital LP are in fact the same disease, whole genome expression analysis was performed on epithelium from 13 patients diagnosed with oral and/or genital LP and normal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…Small proline-rich protein 2B (SPRR2B) is a component of the cornified cell envelope of stratified squamous epithelia (Tarcsa et al 1998), which is also involved in epithelial differentiation (Zimmermann et al 2005). It should be noted that epithelium differentiation is closely associated with OLP, and keratinization is one of the classical features of OLP (Ismail et al 2007;Danielsson et al 2014). In this study, the expression of SPRR2B, CDSN, and LCEs was significantly up-regulated in OLP, coinciding with previous studies (Danielsson et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Small proline-rich protein 2B (SPRR2B) is a component of the cornified cell envelope of stratified squamous epithelia (Tarcsa et al 1998), which is also involved in epithelial differentiation (Zimmermann et al 2005). It should be noted that epithelium differentiation is closely associated with OLP, and keratinization is one of the classical features of OLP (Ismail et al 2007;Danielsson et al 2014). In this study, the expression of SPRR2B, CDSN, and LCEs was significantly up-regulated in OLP, coinciding with previous studies (Danielsson et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that epithelium differentiation is closely associated with OLP, and keratinization is one of the classical features of OLP (Ismail et al 2007;Danielsson et al 2014). In this study, the expression of SPRR2B, CDSN, and LCEs was significantly up-regulated in OLP, coinciding with previous studies (Danielsson et al 2014). Therefore, we suspected that CDSN, LCE3D, LCE3E, and SPRR2B might play a role in OLP through participating in keratinization, differentiation and development of keratinocyte and epithelium.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous investigations have shown that epithelial expression of keratins is altered in OLP compared with normal oral mucosa and this can therefore affect the functions mentioned above: keratin 1 (K1)/keratin 10 (K10) , K14 , keratin 6 (K6)/keratin 16 (K16), and K19 are reported to be upregulated in OLP, whereas keratin 4 (K4) , K4/keratin 13 (K13) , keratin 5 (K5)/keratin 15 (K15) , and K19 are reported to be downregulated. Data on K8 and K18 expression in oral keratinocytes of normal oral mucosa are inconsistent, varying from reports of absence to sporadic presence .…”
mentioning
confidence: 99%